Estimating the obstetric costs of female genital mutilation in six African countries - Taghreed Adam; Heli Bathija; David Bishai; Yung-Ting Bonnenfant; Manal Darwish; Dale Huntington; Elise Johansen
OBJECTIVE: To estimate the cost to the health system of obstetric complications due to female genital mutilation (FGM) in six African countries. METHODS: A multistate model depicted six cohorts of 100 000 15-year-old girls who survived until the age of 45 years. Cohort members were modelled to have various degrees of FGM, to undergo childbirth according to each country's mortality and fertility statistics, and to have medically attended deliveries at the frequency observed in the relevant country. The risk of obstetric complications was estimated based on a 2006 study of 28 393 women. The costs of each complication were estimated in purchasing power parity dollars (I$) for 2008 and discounted at 3%. The model also tracked life years lost owing to fatal obstetric haemorrhage. Multivariate sensitivity analysis was used to estimate the uncertainty around the findings. FINDINGS: The annual costs of FGM-related obstetric complications in the six African countries studied amounted to I$ 3.7 million and ranged from 0.1 to 1% of government spending on health for women aged 15-45 years. In the current population of 2.8 million 15-year-old women in the six African countries, a loss of 130 000 life years is expected owing to FGM's association with obstetric haemorrhage. This is equivalent to losing half a month from each lifespan. CONCLUSION: Beyond the immense psychological trauma it entails, FGM imposes large financial costs and loss of life. The cost of government efforts to prevent FGM will be offset by savings from preventing obstetric complications.